Analisis Potensi Kelongsoran pada Ruas Jalan Raya Pangalengan menggunakan Sistem Informasi Geografis - Muhamad Raffi Rahman; Yuli Suharnoto; Heriansyah Putra (Departemen Teknik Sipil dan Lingkungan, IPB University, 2020)
Indonesian National Board for Disaster Management (BNPB) claimed the landslide incident on 5 May 2015 in Pangalengan District caused gas pipelines owned by PT. Geothermal Star Energy exploded, 9 people died, 154 displaced and 10 houses buried. Based on the facts, it is necessary to make an effort to reduce the risk of landslides by utilizing satellite imagery. The purpose of this study was to identify potential landslides on the Pangalengan highway and make recommendations mitigation actions for the local government. The method used was using 2 estimation system models made by the Directorate of Volcanology and Geological Disaster Mitigation in 2004 and 2005. The result of the DVMBG 2004 showed the very high classification had a percentage of 97.24% and the DVMBG 2005 result showed the high classification reached 53.26% and the very high classification reached 53.26%. The potential for landslides on the Pangalengan road is 98.37%. Recommended mitigation actions were cutting slopes or making soil retaining walls or drainage channel planning.